Correlations between gastrointestinal and oral microbiota in children with cerebral palsy and epilepsy - Huang, Congfu; Chu, Chunuo; Peng, Yuanping; Zhang, Nong; Yang, Zhenyu; You, Jia; Wei, Fengxiang (Frontiers in Pediatrics, 2022)
We here studied the correlation between gut and oral microbiota in children with cerebral palsy and Epilepsy (CPE). We enrolled 27 children with this condition from the social welfare center of Longgang District, collected their oral plaque and stool samples, and analyzed their gut microbiota (GM) and oral microbiota (OM) through 16S rRNA gene sequencing. Taxonomical annotation revealed that the levels of Firmicutes and Bacteroides in the oral cavity were significantly lower in CPE children than in healthy children, whereas the abundance of Actinomycetes increased significantly in CPE children. In addition, Prevotella, Fusobacterium, and Neisseria were the top three abundant genera, representing 15.49%, 9.34%, and 7.68% of the OM and suggesting potential correlations with caries, periodontitis, and malnutrition. For the GM, Bifidobacterium, Bacteroides, and Prevotella were the top three abundant genera in CPE children and probably contributed to the development of chronic inflammation and malnutrition. Furthermore, the OM and GM correlated with each other closely, and the bacterial components of these microbiota in CPE children were remarkably different from those in healthy children, such as Bifidobacterium, Fusobacterium, Bacteroides, and Neisseria. Conclusively, dysbiotic OM can translocate to the intestinal tract and induce GM dysbiosis, suggesting the consistency between OM and GM variations. Altered oral and gut microbial structures have potential impacts on the occurrence of clinical diseases such as periodontitis, caries, and malnutrition.